-x+5=x-11

Simple and best practice solution for -x+5=x-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+5=x-11 equation:


Simplifying
-1x + 5 = x + -11

Reorder the terms:
5 + -1x = x + -11

Reorder the terms:
5 + -1x = -11 + x

Solving
5 + -1x = -11 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
5 + -1x + -1x = -11 + x + -1x

Combine like terms: -1x + -1x = -2x
5 + -2x = -11 + x + -1x

Combine like terms: x + -1x = 0
5 + -2x = -11 + 0
5 + -2x = -11

Add '-5' to each side of the equation.
5 + -5 + -2x = -11 + -5

Combine like terms: 5 + -5 = 0
0 + -2x = -11 + -5
-2x = -11 + -5

Combine like terms: -11 + -5 = -16
-2x = -16

Divide each side by '-2'.
x = 8

Simplifying
x = 8

See similar equations:

| 3b=20 | | 3x+1y=5 | | 8=2(w-2) | | -6u+7= | | 5+d=8d-7 | | 3/5c=2c-7 | | 9-q=5 | | 24/48=50/x | | x+y=10000 | | 12k-11k+2=16 | | 12-8(4-s)+3(s+3)=27 | | 3-2(x-5)=13 | | x(3+2)+9=2x-12 | | 8w+2w-2=18 | | 5c+12-3c=28 | | x-sqrt(40-3x)=0 | | 4x+5(3x-3)=6 | | 2m-4=10+18 | | x(x-3)(x+12)=324 | | 3x+6y=-9 | | 7x+4y=53500 | | 2m-4=10+16 | | F(t)=0.25t^2-0.5t+3.5 | | 26=-7x+5(x+8) | | c+4=3/4 | | 6x-(5x+4)=5x-32 | | -3t-8+7t=35+9t-2 | | 40.5=49+1.7(55-60) | | 6=7x+69 | | 14y=32 | | 10lnx=e^4 | | 6st-7su+5sv= |

Equations solver categories